1999
DOI: 10.1046/j.1432-1327.1999.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection‐dominant and nonaccessible epitopes on cell‐surface receptors revealed by cell‐panning with a large phage antibody library

Abstract: To generate antibodies to defined cell-surface antigens, we used a large phage antibody fragment library to select on cell transfectants expressing one of three chosen receptors. First, in vitro panning procedures and phage antibody screening ELISAs were developed using whole live cells stably expressing the antigen of interest. When these methodologies were applied to Chinese hamster ovary (CHO) cells expressing one of the receptors for a neuropeptide, somatostatin, using either direct cell panning or a strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 37 publications
2
66
0
Order By: Relevance
“…Diversity of the selected HLA-binding phages was determined by colony polymerase chain reaction (PCR) (Red-Taq Readymix; Sigma) and fingerprinting (Bst NI digestion) and confirmed by DNA sequencing with heavy and light chain-specific primers. Fab were expressed, purified, and converted into chimeric IgG molecules exhibiting mouse Fc, using a glutamine synthetase gene expression system (Lonza) as previously described (25). Purity and molecular weights were determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…Diversity of the selected HLA-binding phages was determined by colony polymerase chain reaction (PCR) (Red-Taq Readymix; Sigma) and fingerprinting (Bst NI digestion) and confirmed by DNA sequencing with heavy and light chain-specific primers. Fab were expressed, purified, and converted into chimeric IgG molecules exhibiting mouse Fc, using a glutamine synthetase gene expression system (Lonza) as previously described (25). Purity and molecular weights were determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Methodsmentioning
confidence: 99%
“…22,23 Phagebound V H -V L constructs, selected by successive rounds of enrichment, successfully identified the tumor-associated antigen C1q-R; it is immaterial whether a particular V H -V L combination exists in vivo or is the result of an in vitro construct. Previous studies have reported that nonspecific phage binding interfered with specific selection in both nitrocellulose-bound antigens 17 and immobilized lambda phage cDNA expression libraries hybridized to a phagebound anti-CD30 scfv. 43 Serial dilutions of phage-to-target were needed to calibrate binding specificity.…”
Section: Immunostainingmentioning
confidence: 99%
“…15,16 Combinatorial Ig libraries have most often been used to identify antibodies to either known, purified proteins or proteins specifically engineered to be overexpressed by cells. [15][16][17][18] Identifying previously unrecognized antigens on the surface of whole tumor cells has remained somewhat more difficult for several reasons. Ongoing cell culture and in vitro manipulation may adversely affect preservation of folded 3-D epitopic sites on surface antigens.…”
mentioning
confidence: 99%
“…This method is applicable to cell-surface specific antibody screening, [11] but some reports suggest that the screening results method may be unpredictable. [12] (2) Liquid antigen screening, [13] soluble resistance factors combined with phage antibody, original and combined with the support of antibodies in the packaging phage. This method can better retain the natural conformation of the antigen.…”
Section: Comparison Of Efficiency Of Random Picking Methods and Colonymentioning
confidence: 99%